Accuracy of Xpert Mtb/Rif Ultra for the Diagnosis of Pulmonary Tuberculosis in Children. Issue 10 (October 2018) - Nicol, Mark P.; Workman, Lesley; Prins, Margaretha; Bateman, Lindy; Ghebrekristos, Yonas; Mbhele, Silindile; Denkinger, Claudia M.; Zar, Heather J.
Abstract : We determined the accuracy of the new Xpert MTB/RIF Ultra assay for diagnosis of pulmonary tuberculosis in children, using banked-induced sputum. Sensitivity and specificity were 75.3% and 96.9%, respectively, compared with a culture result from the same specimen. Of those children with microbiologically confirmed tuberculosis (positive Xpert, Ultra or culture), Xpert detected 63.2%, Ultra 73.7% and culture 82.9%.